2015
DOI: 10.1155/2015/389084
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable lifestyle factors are associated with lower pain levels in adults with knee osteoarthritis

Abstract: Pain is the most important osteoarthritis (OA) symptom; however, it is poorly understood and markers of disease severity cannot explain pain variability. With no cure for OA, the authors recognized the need to identify modifiable factors to decrease pain and increase physical function. This study examined factors that characterize OA patients experiencing different levels of pain and investigated the relationships among these factors and OA pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…In the first instance, both interventions had a significant time effect on pain as observed in this study. Both included components that have been shown to directly impact reduction of pain, the leading complaint in individuals with OA and the one that mostly drives health care use [39]. Pain reduction has been proved directly related with reduced disability and, hence, improvement in physical function [17,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first instance, both interventions had a significant time effect on pain as observed in this study. Both included components that have been shown to directly impact reduction of pain, the leading complaint in individuals with OA and the one that mostly drives health care use [39]. Pain reduction has been proved directly related with reduced disability and, hence, improvement in physical function [17,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pain reduction has been proved directly related with reduced disability and, hence, improvement in physical function [17,23]. Connelly et al [39], in a recent cross-sectional survey of 197 individuals with OA, observed a strong negative correlation between physical functioning and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The participants perceived these hardships as knee joint pain-related obstacles to physical activity. Knee joint pain with tenderness and stiffness is one of the most frequent complaints of knee OA patients, which leads to serious limitations on their physical activity [11]. Further, knee OA patients might experience increased physical limitations related to aging and comorbidity, such as diabetes [9].…”
Section: Barriersmentioning
confidence: 99%
“…Previous studies have suggested that knee OA symptoms, including pain, might be key motivational drivers of physical exercise to reduce this pain, as well as barriers to physical activity [9,25]. Therefore, education and guidelines for healthcare professionals should specifically address physical activity levels and/or intensities [11,25] to improve knee OA patients' participation and joint pain reduction [9]. As a result, in response to pain or fatigue, people with OA are likely to modify their activities, not by decreasing frequency, but by adjusting intensity [25].…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation